Ultra-Sparse Binary LDPC Codes with CSK Signals for Increased Data Rates in Future GNSS - Chauvat, Remi; Pena, Axel Garcia; Anghileri, Marco; Floch, Jean-Jacques; Paonni, Matteo (ESA Workshop on Satellite Navigation Technologies and European Workshop on GNSS Signals and Signal Processing (Print), 2018)
Data rate increase in global navigation satellite systems (GNSS) is necessary to provide new features (e.g. precise positioning, security code authentication (SCA) key management). In addition, the data transmission reliability in urban environments can be improved using an induced increase of temporal diversity; the latter being obtained by retransmitting data bits thanks to the data rate improvement. The code shift keying (CSK) modulation is a solution for augmenting data rates of direct-sequence spread-spectrum (DSSS) signals. In addition, last developed GNSS signals make use of modern channel codes in order to further improve the reliability of GNSS data recovery. Hence, this article aims at proposing new binary low-density parity-check (LDPC) codes constructed for the CSK modulation in a bit-interleaved coded modulation (BICM) context. Codes achieving good error rate performance for both BICM and BICM with iterative demapping/decoding (BICM-ID) are presented. The code construction methodology is detailed and the good performance achieved by the constructed codes is assessed in additive white Gaussian noise (AWGN) channel.